The Urgency of the Establishment of Tax Courts at the Regional Level as the Implication of the Movement of the State Capital City - Yadhy Cahyady (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Based on Law Number 14 of 2002 concerning the Tax Court, the settlement of tax disputes is carried out by the Tax Court which is domiciled in the capital city of the country, through procedures and processes that are fast, inexpensive, and simple. Through Law Number 3 of 2022 concerning the State Capital, the Capital of the Archipelago was established as the State Capital. Thus, with the issuance of Law Number 3 of 2022, there will be a transfer of the state capital from Jakarta to the Capital of the Archipelago which will also have implications for the domicile and venue of the Tax Court hearings by Law Number 14 of 2002, the Tax Court Taxes are domiciled in the capital city of the country, and the Tax Court hearings are held at their domicile, and if deemed necessary, they can be conducted elsewhere. The method used in this study is normative juridical, with a statute approach based on secondary data obtained through document studies, to be further analyzed using deductive logic. The legal issues in this study, first, are the implications of moving the capital city of the country to the domicile and venue of the Tax Court trial. Second, why is it necessary to establish a Tax Court at the regional level as an implication of moving the country's capital city? It is hoped that this research will obtain a norm formulation that can provide legal knowledge about the urgency of establishing a Tax Court at the regional level as an implication of moving the state capital from Jakarta to the Nusantara capital.